A review and comparison of reliable unicast routing protocols for mobile ad hoc networks - Sargolzaey, Hadi; Moghanjoughi, Ayyoub Akbari; Khatun, Sabira (International Journal of Computer Science and Network Security, 2009)
An important and essential issue for mobile ad hoc networks is routing protocol design that is a major technical challenge due to the dynamism of the network. Node failures and arbitrary movement of nodes break the routes and lead the frequent operation of rebuilding routes that consume lots of the network resources and the energy of nodes. Many efforts have been made to design reliable routing protocol s that enhance network stability. This paper review and compare some recently published reliable unicast routing protocols, that can be used for selecting appropriate routing protocols, which are suitable for a particular application. Also it will maximize the reliability of the deployed network. Furthermore the proposed methods used in the reviewed protocols, can help designers and researchers for enhancing the reliability of their new routing protocols.